IBN KHALDUN MODEL ON POVERTY: THE CASE OF ORGANIZATION OF ISLAMIC CONFERENCE (OIC) COUNTRIES - Fatoni, Ahlis; Herman, Sebastian; Abdullah, Adam (Journal of Islamic Monetary Economics and Finance, 2019)
If we consider the state of the world economy, especially in the OIC countries, somecountries have to struggle in dealing with the problems of poverty. Hypothetically,the wealth of natural resources is potentially in the welfare of the population, but thefacts on the ground say the situation is another in which it is far from being well-being. This study aims to analyze poverty in OIC countries by using a developmentmodel proposed by Ibn Khaldun. The model consists of six variables: human resourcevariable (proxy HDI), the variable role of government (proxy government spendingin education and health), variable of development (proxy foreign direct investment),state assets variable (proxy for GDP/capita), justice variable (gini index proxy) andsharia variable (a proxy perception index of corruption). This study uses panel dataregression analysis with nine object OIC member countries (Indonesia, Malaysia,Egypt, Azerbaijan, Kazakhstan, Tajikistan, Kyrgyzstan, Turkey and Benin) over theyears from 2010 to 2016. The results showed that the variables of development modelIbn Khaldun significant effect on poverty in OIC countries is development variable, thevariable role of government (proxy for government spending in health sector), justicevariable, wealth nation variable and control variables (unemployment). While the roleof government variable (proxy government spending in the education sector), HRvariables and sharia variables not significant. From these studies, it can be concludedthat not all the variables of development model Ibn Khaldun significant effect onpoverty in OIC countries.